2020
DOI: 10.1089/aid.2020.0020
|View full text |Cite
|
Sign up to set email alerts
|

“My Death Will Not [Be] in Vain”: Testimonials from Last Gift Rapid Research Autopsy Study Participants Living with HIV at the End of Life

Abstract: End-of-life (EOL) HIV cure-related research provides a novel approach to studying HIV reservoirs. The Last Gift is a rapid autopsy research study at the University of California San Diego that enrolls terminally ill people living with HIV (PLWHIV) with a desire to contribute to HIV cure-related research. We conducted in-depth baseline and follow-up interviews with Last Gift study participants. We analyzed interview data applying conventional content analysis. Since summer 2017, 13 participants have been enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…In our discussions, it was noted by a NOK that one participant did not feel comfortable declining blood draws, likely because he felt an obligation towards the study [ 23 ]. Among research participants, feelings of obligation may precipitate from a desire to reciprocate for care and attention received in the past [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our discussions, it was noted by a NOK that one participant did not feel comfortable declining blood draws, likely because he felt an obligation towards the study [ 23 ]. Among research participants, feelings of obligation may precipitate from a desire to reciprocate for care and attention received in the past [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to NOK, by calming their worries and guiding them through the EOL process, the Last Gift team gave them greater confidence and less stress. Existing literature has shown that EOL conversations between family members and physicians may contribute to reducing depression and alleviating grief during the bereavement process [ 23 , 29 ]. Additionally, in a study by Aoun and colleagues, family members who felt supported by palliative care staff before the death of a loved one had a more positive bereavement experience [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the novel and potentially controversial nature of EOL HIV cure-related research, we are conducting extensive empirical research with Last Gift participants and their next-of-kin/ loved ones to understand their perceptions of such research [7,8]. To complement these perspectives, we implemented focus groups in order to understand the perspectives of clinical and rapid research autopsy staff members and the impact that the Last Gift study had on them.…”
Section: Introductionmentioning
confidence: 99%